Articulatory Evidence for the Syllable-final Nasal Merging in Taiwan Mandarin. (December 2021) - Chiu, Chenhao; Lu, Yu-An
Syllable-final nasals /n/ and /ŋ/ in Taiwan Mandarin have been reported to be undergoing merging. Perceptual studies have reported that the alleged merging is context-sensitive and the merging directions are vowel-dependent. These findings have been mostly attributed to dialectal and social factors. The current study uses ultrasonography to capture postures of the entire tongue during the production of syllable-final nasals. The results, though confirming previous findings that the merging directions of syllable-final nasals are vowel-dependent, are best accounted for by the biomechanics of the tongue, as supported by computational 3D model simulations. Furthermore, for some speakers, although nasals were merged in terms of tongue posture, the degrees of nasalization of the preceding vowel were contrastive, suggesting that the merging process may be incomplete.